2017
DOI: 10.7441/joc.2017.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Loan versus Bond Financing of Czech Companies and the influence of the Global Recession

Abstract: European economies are traditionally considered to be bank based regarding the debt financing. However, in times of crises in the bank sector, this feature may indicate a weakness of these economies when the credit squeeze phenomenon may occur and companies' competitiveness might be negatively affected thanks to unstable financing possibilities. In such conditions, a shift from bank loans to bonds might be expected. That is why this paper focuses on mutual development of corporate bond and business loan market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Over the last few decades, global finance markets have gone through a number of financial crises, the most devastating of which include Mexican peso crisis in 1994, Asian flu in 1997, Russian crisis in 1998, Brazilian crisis in 1999, Argentinian crisis in 2001-2002, the USA financial crisis in 2007 and Greek crisis in 2009. The periods of financial contagion have evidently raised the risk of securities (Vychytilova, 2018;Mačí & Valentová Hovorková, 2017; Čulková et al, 2015;Vukovic et al, 2017) and returned the interest in gold as in alternative financial instrument since gold has historically been treated as a standard of high value. Of course, other alternative investments should be mentioned here too (Jurevičienė, & Jakanovytė, 2015;Nuhiu et al, 2017;Mouselli et al, 2016;Śliwiński & Łobza, 2017;Nawrocki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, global finance markets have gone through a number of financial crises, the most devastating of which include Mexican peso crisis in 1994, Asian flu in 1997, Russian crisis in 1998, Brazilian crisis in 1999, Argentinian crisis in 2001-2002, the USA financial crisis in 2007 and Greek crisis in 2009. The periods of financial contagion have evidently raised the risk of securities (Vychytilova, 2018;Mačí & Valentová Hovorková, 2017; Čulková et al, 2015;Vukovic et al, 2017) and returned the interest in gold as in alternative financial instrument since gold has historically been treated as a standard of high value. Of course, other alternative investments should be mentioned here too (Jurevičienė, & Jakanovytė, 2015;Nuhiu et al, 2017;Mouselli et al, 2016;Śliwiński & Łobza, 2017;Nawrocki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is vast academic interest in the methods and effectiveness of corporate financing, where the research could be grouped in to two categories: exploring the market-based financing (research conducted after the financial crisis of 2008-2013): Mertens & Thiemann (2018), Gupta & Gregoriou (2018), Karwowski & Stockhammer (2017), Maci & Valentova Hovorkova (2017), Hardie et al (2013); and narrowing the subject of the analysis to the corporate choice between the market and bank-based funding decision (the research conducted before the financial crisis of 2008-2013): Levine (2002), Fujita (2000), Allen & Gale (2000), Boyd & Smith (1998), Rajan & Zingales (1999), Boot & Thakor (1997), Gerschenkron (1962). The further division and analysis of the factors as affecting the market-based funding decision of the company luck the consistency and major interest in the academic studies.…”
Section: Eis 13/2019mentioning
confidence: 99%
“…Corporations come to the bond market to address their financing needs where long-term oriented and cost-effective financing forms the continuity of the company and builds its competitiveness in the market. The academic literature provides broad motivation for corporate debt issuing, where Maci & Valentova Hovorkova (2017) named the riskiness of businesses and costs of moni¬toring Literature Reviews for the creditor, the accessibility of loan ratings of businesses, the overall eco¬nomic maturity of the country, the size, or phases, of life cycles of businesses, the communica¬tion of businesses with the investor community, the terms of the loan contract factors. Tocelovska (2008) revealed that efficient competition to bank funding, long-term financing, improvement of the cash flow by decreasing the cost of debt, optimisation of the financial structure, and efficient ownership structure among the main factors.…”
Section: Eis 13/2019mentioning
confidence: 99%
“…The companies using debt financing of the transaction may reduce their tax base by increasing the share of debt financing (see Huyghebaert & Luypaert, 2010). Because financing companies through bank loans is more common in the Czech Republic than through issuing bonds, the bank loans to assets ratio was analysed (see, for example, Mačí & Valentová Hovorková, 2017).…”
Section: The Value •mentioning
confidence: 99%